STATUS OF URBAN SPRAWLS IN VISAKHAPATNAM CITY - challabathula, Dr.subha kumar; MARAPATLA, GAMGAYYA (IJRDO-Journal of Applied Science, 2018)
Visakhapatnam is a fast developing port city and recording rapid rate of urbanization. With increasing population and ever increasing demand of land the new extensions of the city have taken place. It is expanding in all possible directions resulting in large scale changes in urban land use which affects the physical and social environment of the city. The city has gained real importance from 1970 onwards due to location of many industries which had resulted in considerable spread with the establishment of new residential colonies. The spatial growth of the city has been restricted by physical barriers on the north, south and east. Visakhapatnam city is growing along the southwest, northwest and northeast directions. The rate of land development is as high as 789% during the 35 year of study period while the population growth rate is 266%. Thus the per capita land consumption has increased markedly and it is true especially in the peripheral zones a strong indicator of sprawl. The distribution of population density in various wards also justifies the above characteristic of sprawl – “dense core and dispersed suburbs”. The higher entropy values at different points during the study period indicate high rate of sprawl even in early seventies and sustained throughout. Therefore the entropy approach is proved to be efficient to identify measure and monitor the spatio-temporal patterns of urban phenomena. This paper analyzes the urban sprawl causes and consequences.